Food packing and food alterations : the user-oriented approach - Parisi, Salvatore (Smithers Rapra, 2012)
HACCP studies seem to highlight the role of food productions. On the other hand, detailed information about packaging materials are needed. This lack of information is very evident for official inspectors (hygiene and preventive medicine), veterinary auditors and food operators. Consequently, the role of food packaging is known but its implications are often difficult to be understood. The first objective of this title is to provide detailed and comprehensible information about packaging materials